Cigarette smoke inhalation patterns and bronchial reactivity. Issue 1 (January 1988) - Taylor, D R; Reid, W D; Paré, P D; Fleetham, J A
Abstract : The manner in which a cigarette is smoked varies considerably between individuals and may be an important determinant of the altered bronchial reactivity observed in cigarette smokers. Twenty smokers were examined to determine the relationship between cigarette smoke inhalation patterns and bronchial reactivity. Inhalation patterns were measured non-invasively with a respiratory inductive plethysmograph and these were related to the provocative concentration of histamine that caused a 20% fall in FEV1 (PC20) and to the cough threshold for inhaled citric acid. Histamine PC20 values were inversely correlated with depth and rate of inhalation. Cough threshold was inversely correlated with greater cigarette consumption and with depth of inhalation.